load       x                       ac = x

sto         t                        t = x

li            3                       ac = 3

add        t                        ac = x + 3

sto         t                        t = x + 3

load       x                       ac = x

sto          t + 1                 t + 1 = x

load       y                        ac = y

sto         t + 2                   t + 2 = y

li            2                        ac = 2

add         t + 2                  ac = y + 2

add         t + 1                  ac = x + ( y + 2 )

add         t                        ac = ( x + 3 ) + ( x + ( y + 2 ) )

 

Retour